Platform Stickiness in a Spatial Voting Model - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
The spatial voting approach is extended to account for the existence of a loyalty effect driving the choice of parties' platforms during elections. There emerges a non-linear relationship between these variable, whereby a party sticking to its historical heritage may lose to a rival more keen to approach the position of the median voter, whose pivotal role is also investigated.
Keywords: 330